Advanced strawberry farming: effect of UV light and fruiting characteristics on resource efficiency in Vertical Indoor Farming - Sabine Wittmann; Ivonne Jüttner; Inga Mewis; Nadja Förster; Senthold Asseng; Heike Mempel (Journal of Applied Botany and Food Quality)
Vertical Indoor Farming (VIF) offers a potential for high-quality strawberry production, but resource efficiency data still need to be provided. Three strawberry cultivars with different fruiting characteristics, one Ever-bearing cultivar and two June-bearing (high- yielding and an old, traditional) cultivars, and two light treatments were investigated: artificial white LED light with an additional 2% UVA (365 nm) and white LED light alone. The Ever-bearing cultivar demonstrated significantly higher efficiencies for surface use efficiency (SUE) of 15.2 kg fresh weight m-2 a-1, water use efficiency (WUE) of 291 g fresh weight l-1, and energy use efficiency (EUE) of 10.6 g fresh weight kWh-1, due to a high harvest index of up to0.8 and a low proportion of non-marketable fruit. However, the total energy demand of a container VIF is high, with 4.4-6.4 kWh m-2 d-1. Additional UVA radiation did not significantly alter the Ever-bearing cultivar’s performance. At the same time, multiple harvests and a low proportion of non-marketable fruits led to a higher cumulative yield and increased efficiency, making it a promising choice for strawberry cultivation in VIF.